Comparison of seed dormancy breaking of Eusideroxylon zwageri from Bali and Kalimantan soaked with sodium nitrophenolate growth regulator - Jhon Hardy Purba; Nanang Sasmita; Liris Lis Komara; NOH NESIMNASI (Nusantara Bioscience, 2019)
Abstract. Purba JH, Sasmita N, Komara LL, Nesimnasi N. 2019. Comparison of seed dormancy breaking of Eusideroxylon zwageri from Bali and Kalimantan soaked with sodium nitrophenolate growth regulator. Nusantara Bioscience 11: 146-152. Eusideroxylon zwageri is a very strong and durable wood, which can be used as building materials. This wood plant needs 6-12 months to germinate, but it can be shorted with special treatment (e.g. cracking). Therefore, it is important to conduct research to stimulate E. zwageri seed germination using sodium nitrophenolate growth regulator. The purpose of this study was to analyze the comparison of the fastest time to breaking E. zwageri seed dormancy from the Bali and Kalimantan island. The research method was factorial randomized block design, using the X factor (soaking time) and Y factor (sodium nitrophenolate growth regulator). There were four soaking time treatment, i.e., immersed (soaked in a really short time), 12 and 24 hours soaking time. While the Y factor was the concentration of sodium nitrophenolate with 4 treatments: without sodium nitrophenolate solution or 0 mL (control), soaked in a 1 mL/L of water, 2 mL/L of water and 3 mL/L of water solution. The study results showed the best treatment of E. zwageri seeds germination speed was soaked for 24 hours, and by giving 0,3% sodium nitrophenolate concentration, while the interactions of both showed no significant effect. The soaked time treatment, sodium nitrophenolate concentration, and the interaction of both show no significant effect on germination percentage. The breaking of E. zwageri seed dormancy from Kalimantan has a shorter time to germinate than E. zwageri seeds from Bali.